2015
DOI: 10.1002/aqc.2606
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of lake use by breeding common scoters in Scotland

Abstract: ABSTRACT1. Many populations of sea-ducks, which typically winter at sea but breed on fresh water, are declining. Numbers of common scoters Melanitta nigra (L.) breeding in Scotland halved between 1995 and 2007, despite most breeding sites having special conservation status. To identify potential conservation measures, a 3-year study was conducted, investigating correlates of lake use by scoters.2. At 26 scoter breeding lakes, food abundance (macroinvertebrates) and foraging habitats (substrates, water depth) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Instead, they suggested that adaptive management might work best in addressing smaller, more tractable problems, ‘in simple systems in which existing data suggest the causal relationships, and where contrasting management regimes can be introduced to test the hypothesized relationships’ (Rist et al, 2013, p. 14). Our situation is quite similar to this, with our single‐species focus and current management trials that are based on previous research, including the lake selection study of Hancock et al (2016). An adaptive management focus on one species or a specific guild within an ecosystem can nevertheless bring multiple wider ecological and ecosystem services benefits (King et al, 2009).…”
Section: The Secondary Impacts Of the Study: Towards Adaptive Managemsupporting
confidence: 74%
See 4 more Smart Citations
“…Instead, they suggested that adaptive management might work best in addressing smaller, more tractable problems, ‘in simple systems in which existing data suggest the causal relationships, and where contrasting management regimes can be introduced to test the hypothesized relationships’ (Rist et al, 2013, p. 14). Our situation is quite similar to this, with our single‐species focus and current management trials that are based on previous research, including the lake selection study of Hancock et al (2016). An adaptive management focus on one species or a specific guild within an ecosystem can nevertheless bring multiple wider ecological and ecosystem services benefits (King et al, 2009).…”
Section: The Secondary Impacts Of the Study: Towards Adaptive Managemsupporting
confidence: 74%
“…Like most sea ducks, common scoters winter at sea but breed in freshwater habitats, and feed by diving for invertebrate prey. The scoter lake‐use study published in Aquatic Conservation: Marine and Freshwater Ecosystems (AQC) (Hancock, Robson, Smith, & Douse, 2016) investigated correlates of lake use in the two remaining scoter breeding concentrations in Scotland. In the West Highlands, scoters breed at large (~300–1,300 ha) valley‐bottom lakes managed for hydropower generation (within the Great Glen scheme; Scottish and Southern Energy [SSE], 2005).…”
Section: The Original Study: Correlates Of Lake Use By Breeding Commomentioning
confidence: 99%
See 3 more Smart Citations